Rapid Excavation and Tunneling Conference 2013 proceedings - DiPonio, Michael A.; Dixon, Chris (Society for Mining Metallurgy and Exploration, 2013)
Every two years, industry leaders and practitioners from around the world gather at the Rapid Excavation and Tunneling Conference (RETC), the authoritative program for the tunneling profession. This comprehensive book includes more than 100 papers from industry experts, highlighting their most recent projects and sharing real-world experiences that will keep you up to date on the latest tunneling trends and technologies.
Keywords: Tunneling -- Congresses.; Excavation -- Congresses.; Underground construction -- Congresses.; elektronické knihy; electronic books